PENERAPAN VIDEO ANIMASI DALAM PENCEGAHAN KEKERASAN SEKSUAL ANAK JALANAN : Penerapan Video Animasi Dalam Pencegahan Kekerasan Seksual Anak Jalanan - Suryati; Setyawan, Aris; Sari, Dian Nur Adkhana; Al'adawiyah, Airabi'ah (Jurnal Pengabdian Masyarakat Kesehatan Terkini, 2024)
Street children are children who spend most of their time doing daily life activities on the streets, either to make a living or roam the streets and other public places. One of the problems that threatens street children is sexual violence, where they often become victims due to the situation, conditions and environment around them. Sexual violence with child victims can have psychosocial impacts, such as children having negative self-assessment and life, having inappropriate sexual behavior, using illegal drugs and consuming alcohol, and having bad relationships with their family or the surrounding environment. The service method in the form of health education using video media was chosen to make it easier for children to receive material about preventing sexual violence. The purpose of this community service is to increase street children's knowledge about preventing sexual violence. The target was street children assisted by the Yayasan Rumah Impian Yogyakarta, a total of 30 children. The results of the service include an increase in knowledge between before and after being given health education. The plan for the next stage is to always increase motivation for children to prevent sexual violence from occurring, so as to reduce the incidence of sexual violence against children.